The Effectiveness of Poverty Alleviation in Increasing Economic Development in Kudus Regency - Azzahra, Lailatul Maulida; Hakim, M. Arif; Rahmawati, Yuliana Dewi (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2023)
This research is motivated by the relationship between poverty alleviation and economic development in Kudus Regency. Kudus Regency has very significant challenges to high poverty and economic disparities in the Kudus Regency area from 2021 to 2022. This study aims to analyze or find out the effectiveness of poverty alleviation efforts that have been carried out by the Kudus Regency government in the context of improving the economy. The research method used was a qualitative descriptive analysis method by obtaining data from the Central Bureau of Statistics (BPS). The data was used to analyze the effectiveness of poverty alleviation efforts, the amount of poverty, and the factors that cause poverty in Kudus Regency. The research illustrates that poverty in Kudus Regency is caused by factors such as lack of skills or expertise, people's mindset is too stagnant towards work, consumptive behavior, and low production productivity. Poverty alleviation efforts that have been carried out by the Kudus Regency government through programs including UMKM, village funds per sub-district, and the SDGs program which have a positive impact on reducing poverty and can improve the welfare of the people of Kudus Regency so that the relationship with economic development and poverty alleviation certainly requires an approach comprehensive.